BRICS and Digitally Just and Inclusive Futures - Bricsology (Journal of BRICS Studies)
As the BRICS (Brazil, Russia, India, China, and South Africa) countries gather for the 2023 Summit in August 2023, they are confronted with the task to deepen economic cooperation in line with the BRICS Economic Partnership Strategy. Key to this is the building of a BRICS-wide digital economy that enables inclusion and dynamism.  They see themselves as committed to driving digital transformation, harnessing opportunities and mitigating challenges they face in regard to digital technologies. They recognize the importance of digital inclusion and connectivity as economic growth and social development drivers. Initiatives such as India's Digital India program, China's Belt and Road Initiative, and South Africa's National Integrated ICT Policy emphasize expanding digital infrastructure and improving access to bridge the digital divide (Kaplinsky, 2017).